Fine-root carbon and nitrogen concentration of European beech (Fagus sylvatica L.) in Italy Prealps: possible implications of coppice conversion to high forest - Terzaghi, Mattia; Montagnoli, Antonio; Di Iorio, Antonino; Scippa, Gabriella S.; Chiatante, Donato (Frontiers in Plant Science, 2013)
Fine-root systems represent a very sensitive plant compartment to environmental changes. Gaining further knowledge about their dynamics would improve soil carbon input understanding. This paper investigates C and N concentrations in fine roots in relation to different stand characteristics resulting from conversion of coppiced forests to high forests. In order to evaluate possible interferences due to different vegetative stages of vegetation, fine-root sampling was repeated 6 times in each stand during the same 2008 growing season. Fine-root sampling was conducted within three different soil depths (0-10; 10-20; and 20-30 cm). Fine-root traits were measured by means of WinRHIZO software which enable us to separate them into three different diameter classes (0-0.5, 0.5-1.0 and 1.0-2.0 mm). The data collected indicate that N concentration was higher in converted stands than in the coppiced stand whereas C concentration was higher in the coppiced stand than in converted stands. Consequently the fine-root C:N ratio was significantly higher in coppiced than in converted stands and showed an inverse relationship with fine-root turnover rate, confirming a significant change of fine-root status after the conversion of a coppice to high forest.